Performance of Fiscal Accounts in South Africa in a Cross-Country Setting - Aydin, Burcu (IMF Working Papers; Working Paper ;, 2010)
This paper analyzes the cyclical fluctuations in South Africa in a cross-country context, and studies the impact of the output gap by controlling for export intensity, the debt burden, asset prices, and banking crises. Results show that South Africa's revenue performance was outstanding during the mid-2000s, and the recent decline in revenue was one of the least among the emerging and advanced markets. Results on the elasticity of tax revenue show that South Africa's elasticity is higher during business upturns, indicating good prospects for recovering the revenue lost during the global financial crisis.